THE USE OF CONJUNCTIONS IN STUDENTS’ CONTINUOUS WRITING: A SYSTEMIC FUNCTIONAL LINGUISTIC STUDY - BABURA, Adamu Isah; IDRIS, Adamu (EBSU Journal of Social Sciences and Humanities, 2024)
This study sets out to examine the use of elaborative conjunctions in students’ continuous writing. The population of the study constitutes 30 students who were in level 200 at the Department of English and Literary Studies, Bayero University, Kano. Using simple random sampling technique, a total of 25 students were chosen as the sample size. The selected participants were given an essay writing tasks of not more than two pages. The essays were marked by four veteran teachers of English with the view of identifying instances of mis(use) of elaborative conjunctions. The sentences that feature the use of conjunctions were analysed as data using the Systemic Functional Linguistics associated with Michael Halliday. The findings of the study reveal that most of the students have little or no problem in using the elaborative conjunctions. This is so because of the 100 misuse of conjunctions found in the essays, only 13 cases involve the elaborative conjunctions. Thus, the study concludes that as far as the use of the elaborative conjunctions is concerned, the analysed essays have satisfied the criteria of coherence and cohesion. In other words, students at level 200 in universities have a reasonable mastery of the usage of elaborative conjunctions.